Self-healing double-layer hydrogel for promoting healing of diabetic wounds as well as preparation method and application of self-healing double-layer hydrogel
By developing a self-healing bilayer hydrogel, the problem of difficulty in healing diabetic wounds is solved by using photosynthetic oxygen production and photothermal antibacterial effects of microalgae cells and metal ion-humidic acid coordination nanoparticle complexes, and the problem of difficulty in healing is achieved. It has the effects of oxygen-release, antioxidant and antibacterial effects, and is simple in process and low in cost.
Patent Information
- Application Number
- CN202411551605.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-02-07
AI Technical Summary
Diabetic wounds are prone to bacterial infection, hypoxia and excessive reactive oxygen species, which lead to delayed healing. The photosensitizers of existing photothermal therapy have high cost, inconvenient preparation, unsatisfactory biodegradability and potential toxicity limitations, and nanoenzymes The ROS removal ability is limited and the antibacterial effect is poor.
Develop a self-healing bilayer hydrogel with microalgae cells in the inner layer and a metal ion-humidic acid-coordinated nanoparticle complex, combining antioxidant and release through photosynthetic oxygen production and photothermal antibacterial effects. Oxygen effect promotes wound healing.
It has achieved oxygen-release, antioxidant and antibacterial effects on diabetic wounds, promoted wound healing, and has a simple process and low cost, which is suitable for large-scale promotion.
Smart Images

Figure BDA0005115237860000071 
Figure BDA0005115237860000081 
Figure BDA0005115237860000082
Abstract
Description
Technical Field
[0001] The invention relates to a self-healing double-layer hydrogel for promoting diabetic wound healing and a preparation method and application thereof, belonging to the technical field of medical materials for surgical supplies containing macromolecular materials. Background Art
[0002] The diabetic wound microenvironment is characterized by high sugar, susceptibility to bacterial infection, hypoxia, and the presence of excessive reactive oxygen species (ROS), which are the main reasons for delayed healing of diabetic wounds. Diabetic wounds are chronic wounds in which the damaged skin is often infected by exogenous microorganisms or bacteria that normally parasitize the skin. The emergence of infection may delay wound healing due to the aggravation and prolongation of the inflammatory phase. Therefore, how to treat bacterially infected chronic diabetic wounds has become an important issue that needs to be addressed. Light-based photothermal therapy (PTT) has the advantages of simple operation, spatiotemporal selectivity, and non-invasiveness. It has become a promising method to alleviate wound infection and accelerate wound healing in the past few years. Although satisfactory results can be achieved in preventing wound infection, the currently used photosensitizers (PS) are limited in clinical application by high cost, inconvenient preparation, unsatisfactory biodegradability, and potential toxicity. In addition, these PS lack biological activities that further promote wound healing, such as antioxidant activity and scavenging reactive oxygen species.
[0003] Another major factor affecting diabetic wound healing is wound hypoxia, which can be alleviated by inorganic oxygen-producing nanomaterials, such as nanozymes with catalase activity, which produce oxygen by decomposing H2O2. However, the disadvantage of this method is that oxygen is released suddenly and the utilization rate is low. In response to the excessive reactive oxygen species (ROS) in the diabetic wound microenvironment, nanozymes, as one of the effective reactive oxygen species (ROS) scavenging biomaterials, have received widespread attention in promoting diabetic wound healing. However, their ROS scavenging ability is quite limited, as well as their ROS-dependent antibacterial effects on bacteria or immune cells, which leads to poor and uncontrolled antibacterial effects.
[0004] Therefore, developing a wound healing dressing that integrates oxygen release, anti-oxidation and antibacterial properties has certain application value. Summary of the invention
[0005] The present invention provides a self-healing double-layer hydrogel for promoting diabetic wound healing, and a preparation method and application thereof. The double-layer hydrogel has an inner and outer layer, which can not only exert a photothermal antibacterial effect through the outer layer hydrogel, but also relieve hypoxia through the inner layer hydrogel. The inner layer hydrogel can block the direct contact between the outer layer hydrogel and the skin, preventing excessive heat from causing side effects on the skin. The double-layer hydrogel dressing is a programmed wound healing double-layer hydrogel dressing that integrates oxygen release, anti-oxidation and antibacterial properties.
[0006] One of the purposes of the present invention is to provide a self-healing double-layer hydrogel for promoting diabetic wound healing, comprising an inner and outer layer, wherein the inner layer is a self-healing hydrogel in which microalgae cells are evenly distributed, and the outer layer is a self-healing hydrogel in which metal ion-humic acid coordinated nanoparticle complexes are evenly distributed, wherein:
[0007] The self-healing hydrogel is formed by self-crosslinking of a macromolecular polymer containing an aldehyde group and a macromolecular polymer containing an amino group.
[0008] In the double-layer hydrogel of the present invention, the inner layer is the side in contact with the skin, and the outer layer is the side away from the skin.
[0009] In the double-layer hydrogel of the present invention, the inner and outer layers of the hydrogel matrix are made of the same raw materials and both have self-healing properties, so that the two layers are combined into a whole and synergistically used for wound healing.
[0010] In the double-layer hydrogel of the present invention, the inner layer mainly plays the role of photosynthetic oxygen production and anti-oxidation, and also has a certain heat buffering effect.
[0011] In the double-layer hydrogel described in the present invention, the outer layer mainly exerts a photothermal antibacterial effect.
[0012] In the double-layer hydrogel of the present invention, the macromolecular polymer containing aldehyde groups is one or more of oxidized hyaluronic acid, oxidized sodium alginate, oxidized konjac glucan and oxidized dextran.
[0013] Preferably, the macromolecular polymer containing aldehyde groups is oxidized konjac glucan.
[0014] Furthermore, the oxidation degree of the oxidized konjac glucan is 40-50%.
[0015] Furthermore, the preparation method of the oxidized konjac glucan is as follows: 2.5 g of konjac glucan (KG) is dissolved in 300 mL of pure water, stirred and heated in a water bath at 40° C. until KG is completely dissolved, then 5 mL of sodium periodate (0.35 g / mL) is added dropwise, and stirred at 300 to 600 rpm for 6 to 12 hours at 37° C. in the dark, after which 12.5 mL of ethylene glycol is added to terminate the reaction, and the mixture is stirred for 2 hours; the mixture is loaded into a dialysis membrane (MWCO: 8K to 14K), and the mixture is dialyzed in deionized water for 3 to 7 days; finally, the dialyzate is centrifuged at 1000 rpm / min for 15 minutes, and the supernatant is taken for freeze-drying to obtain purified oxidized konjac glucan (OKG).
[0016] In the double-layer hydrogel of the present invention, the macromolecular polymer containing amino groups is one or more of carboxymethyl chitosan, chitosan and polylysine.
[0017] Preferably, the macromolecular polymer containing amino groups is carboxymethyl chitosan.
[0018] In the double-layer hydrogel of the present invention, the microalgae cells are one or more of cyanobacteria, green algae, red algae, brown algae, cryptophytes, dinophytes, chrysophytes, xanthophytes, diatoms, euglenophytes and charophytes.
[0019] Preferably, the microalgae cells are one or more of Cyanobacteria and Chlorophyta.
[0020] More preferably, the microalgae cell is Chlamydomonas reinhardtii.
[0021] In the double-layer hydrogel described in the present invention, the preparation method of the metal ion-humic acid coordinated nanoparticle complex is: adding the humic acid aqueous solution dropwise into the metal ion compound aqueous solution, stirring at 500-1000 rpm for 3-4 hours, centrifuging, washing the precipitate with water twice or more, and freeze-drying to obtain the metal ion-humic acid coordinated nanoparticle complex.
[0022] In the above technical solution, the mass volume ratio of the metal ion compound to the aqueous solution is 0.5g:10-40mL.
[0023] In the above technical solution, the mass volume ratio of humic acid to aqueous solution is 0.5g:10-40mL.
[0024] The process steps involved in the preparation method of the metal ion-humic acid coordinated nanoparticle complex of the present invention are all carried out at room temperature.
[0025] In the above technical solution, the metal ions are one or more of gold, platinum, ruthenium, rhodium, iridium, silver, copper and iron ions.
[0026] Preferably, the metal ions are silver ions.
[0027] In the above technical solution, the humic acid is one or more of humic acid, fulvic acid and humin.
[0028] Preferably, the humic acid is fulvic acid.
[0029] In the double-layer hydrogel of the present invention, the condition for the photosynthetic oxygen production effect in the inner layer hydrogel is a light intensity of 2000-5000lx.
[0030] In the double-layer hydrogel of the present invention, the condition for the outer layer hydrogel to exert the photothermal antibacterial effect is to be irradiated with near-infrared light with a wavelength of 808 nm.
[0031] Another object of the present invention is to provide a method for preparing the self-healing double-layer hydrogel for promoting diabetic wound healing, comprising the following steps:
[0032] Step 1: adding a certain amount of live microalgae cells to a polymer macromolecular solution containing an aldehyde group to obtain a mixed solution A, and then adding a polymer macromolecular solution containing an amino group to the mixed solution A, cross-linking at room temperature, to obtain an inner layer hydrogel with antioxidant and photosynthetic oxygen production effects;
[0033] Step 2: Add a certain amount of metal ion-humic acid coordinated nanoparticle complex to the polymer macromolecular solution containing aldehyde groups to obtain a mixed solution B, and then add the polymer macromolecular solution containing amino groups to the mixed solution B to obtain an outer layer hydrogel solution with photothermal antibacterial effect, which is then quickly poured onto the gelled inner layer hydrogel obtained in step 1, and continue to cross-link at room temperature to obtain a self-healing double-layer hydrogel that promotes diabetic wound healing.
[0034] Preferably, the cross-linking temperature is 25°C.
[0035] In the method for preparing the double-layer hydrogel of the present invention, in step 1, the concentration of the living microalgae cells is 5×10 7 ~5×10 8 / mL, the concentration of the polymer macromolecule solution containing aldehyde groups is 0.5-3wt%, and the concentration of the polymer macromolecule solution containing amino groups is 3-6wt%.
[0036] In the preparation method of the double-layer hydrogel of the present invention, in step 2, the concentration of the metal ion-humic acid coordinated nanoparticle complex is 0.4-2 mg / mL, the concentration of the polymer macromolecular solution containing aldehyde groups is 0.5-3wt%, and the concentration of the polymer macromolecular solution containing amino groups is 3-6wt%.
[0037] In the method for preparing the double-layer hydrogel of the present invention, the solution system is a phosphate buffer solution system with a pH of 7 to 8.
[0038] Preferably, the solution system is a phosphate buffer solution system with a pH of 7.4.
[0039] Another object of the present invention is to provide the use of the self-healing double-layer hydrogel for promoting diabetic wound healing in the preparation of chronic diabetic wound dressings.
[0040] The hydrogel matrix in the double-layer hydrogel obtained by the present invention is composed of polymer macromolecules containing aldehyde groups and polymer macromolecules containing amino groups. The hydrogel matrix uses the Schiff base principle and has good self-healing, biocompatibility and degradability. At the same time, the high light transmittance of the matrix retains the photosynthetic oxygen production of microalgae, and the addition of microalgae improves the water retention rate of the hydrogel, which is more conducive to wound healing. The preparation process of the photothermal agent metal ion-humic acid coordinated nanoparticle complex is simple and low in cost. The metal ion coordination agent humic acid gives the photothermal agent certain antioxidant properties, and the excellent photothermal conversion performance of the metal ion-humic acid coordinated nanoparticle complex can further enhance the antibacterial effect of the antibacterial hydrogel, and it has great development potential for use in wound dressings for bacterially infected wounds.
[0041] Compared with the prior art, the present invention has the following beneficial effects:
[0042] 1. The double-layer hydrogel prepared by the present invention not only has inherent broad-spectrum antibacterial activity, but also retains the advantages of hydrogel in tissue regeneration, and can continuously act on the surface of diabetic bacterial-infected wounds to achieve positive effects such as oxygen production, anti-oxidation, sterilization and moisturizing to promote wound healing.
[0043] 2. The present invention introduces a photothermal agent metal ion-humic acid coordinated nanoparticle complex for PTT antibacterial treatment, which generates local high temperature under the irradiation of near-infrared light, leading to bacterial damage and death. The metal ion coordinated agent humic acid not only gives the photothermal agent certain antioxidant properties, but also avoids the introduction of common toxic photoinitiators.
[0044] 3. The present invention introduces oxygen-generating agents and antioxidants into microalgae cells for photosynthetic oxygen production. Under the irradiation of 2000-5000lx white light, oxygen is continuously produced, thereby alleviating the hypoxic microenvironment of diabetic wounds. In addition, the microalgae cells also have certain antioxidant properties, which can remove excessive ROS on the wound surface and accelerate the healing process of the wound.
[0045] 4. The preparation processes of the metal ion-humic acid coordinated nanoparticle complex and the double-layer hydrogel disclosed in the present invention are simple to operate, low in cost and mild in reaction conditions, and are suitable for large-scale promotion and use. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] Figure 1 This is the transmission electron microscopy image of Ag-FANPs obtained in Example 1.
[0047] Figure 2 This is the scanning electron microscope elemental analysis diagram of Ag-FANPs obtained in Example 1.
[0048] Figure 3 This is a diagram of the gelation experiment of the double-layer hydrogel obtained in Example 1.
[0049] Figure 4 This is the photothermal temperature rise diagram of Ag-FANPs obtained in Example 1 at different concentrations.
[0050] Figure 5 Visualized thermal imaging images of Ag-FANPs obtained in Example 1 at different concentrations.
[0051] Figure 6 This is a graph showing the bactericidal effect of Ag-FANPs obtained in Example 1 on S. aureus at different concentrations.
[0052] Figure 7 This is a graph showing the bactericidal effect of Ag-FANPs obtained in Example 1 on E.coil at different concentrations.
[0053] Figure 8 This is a test chart of dissolved oxygen production by Chlamydomonas reinhardtii at different concentrations in Example 1.
[0054] Fig. 9 This is a test chart of the antioxidant capacity of Chlamydomonas reinhardtii at different concentrations in Example 1.
[0055] Fig.10 This is a frequency scanning analysis diagram of the double-layer hydrogel obtained in Example 1.
[0056] Fig.11 This is a step strain analysis diagram of the double-layer hydrogel obtained in Example 1.
[0057] Fig.12 This is the photothermal heating diagram of the double-layer hydrogel encapsulated Ag-FANPs obtained in Example 1.
[0058] Fig.13 This is a visualized thermal imaging image of the double-layer hydrogel encapsulating Ag-FANPs obtained in Example 1.
[0059] Fig.14 This is a diagram showing the bactericidal effect of the double-layer hydrogel obtained in Example 1 on S. aureus.
[0060] Fig.15 This is a diagram showing the bactericidal effect of the double-layer hydrogel obtained in Example 1 on E.coil.
[0061] Fig.16 This is a test chart of dissolved oxygen generation of the double-layer hydrogel obtained in Example 1.
[0062] Fig.17 This is a blood compatibility test diagram of the double-layer hydrogel obtained in Example 1.
[0063] Fig.18 This is a flowchart of the treatment of bacterially infected rat diabetic wound model using the double-layer hydrogel obtained in Example 1.
[0064] Fig.19 This is a diagram showing the treatment results of the double-layer hydrogel obtained in Example 1 on a bacterially infected rat diabetic wound model.
[0065] Fig. 20 This is a smear plate of animal wound tissue during the treatment of bacterial-infected rat diabetic wound model by the double-layer hydrogel obtained in Example 1. DETAILED DESCRIPTION
[0066] The following non-limiting embodiments may enable a person skilled in the art to more fully understand the present invention, but are not intended to limit the present invention in any way.
[0067] The test methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.
[0068] Example 1
[0069] A method for preparing a self-healing double-layer hydrogel for promoting diabetic wound healing comprises the following steps:
[0070] (1) Synthesis of silver-fulvic acid nanoparticles (Ag-FANPs)
[0071] 1.0 g of silver nitrate (AgNO3) was dissolved in distilled water (10 mL), and then 0.5 g of fulvic acid (FA) was dissolved in distilled water (10 mL). The obtained FA solution was then added dropwise to the AgNO3 solution. After stirring at 800 rpm for 3 to 4 h, the obtained solution was centrifuged, and the precipitate was washed with water for more than three times and freeze-dried to obtain Ag-FANPs.
[0072] The transmission electron microscopy results and scanning electron microscopy elemental analysis results of Ag-FANPs are shown in Figure 1 and Figure 2 It can be seen that: Ag-FANPs are round particles with uniform size and good dispersion, and the particle size is about 90nm; the content of O and C elements is >90%, indicating that the FA content in Ag-FANPs is large, which is expected to reduce the high toxicity caused by silver ions and improve the biocompatibility of nanoparticles.
[0073] (2) Preparation of Oxidized Konjac Glucan (OKG)
[0074] First, 2.5 g of konjac glucan (KG) was dissolved in distilled water (300 mL), stirred and heated in a 40°C water bath until KG was completely dissolved, then 5 mL of sodium periodate (0.35 g / mL) was added dropwise, and 12.5 mL of ethylene glycol was added to terminate the reaction after stirring at 500 rpm for 6 h in the dark at 37°C, and the mixture was stirred for 2 h. Next, the mixture was loaded into a dialysis membrane (MWCO: 8K-14K), and the mixture was dialyzed in deionized water for 3 days. Finally, the dialyzate was centrifuged at 1000 rpm / min for 15 min, and the supernatant was freeze-dried to obtain purified OKG.
[0075] (3) Preparation of inner layer C-KGCM hydrogel
[0076] A certain amount of carboxymethyl chitosan (CMCS) powder was added to a phosphate buffer solution at pH = 7.4 and heated in a 40°C water bath with constant stirring until the final CMCS concentration was 4 wt%. In addition, an appropriate amount of OKG powder was dissolved in a phosphate buffer solution at pH = 7.4 and heated in a 40°C water bath to obtain an OKG solution with a concentration of 1.0 wt%. 8 The Chlamydomonas reinhardtii with a concentration of 0.174 g / mL was centrifuged, and the settled algal cells, 0.5 mL CMCS solution and 0.5 mL OKG solution were uniformly mixed at 25°C to obtain an inner layer C-KGCM hydrogel solution, which was observed at 25°C and waited for gelation to obtain C-KGCM hydrogel, wherein the gelation time was 5.5 min.
[0077] (4) Preparation of outer layer Ag-FANPs-KGCM hydrogel solution
[0078] A certain amount of CMCS powder was added to a phosphate buffer solution of pH = 7.4, and heated in a 40°C water bath with constant stirring until the final CMCS concentration was 4wt%. In addition, an appropriate amount of OKG powder was dissolved in a phosphate buffer solution of pH = 7.4, and also heated in a 40°C water bath to obtain an OKG solution with a concentration of 1.0wt%. Subsequently, 0.4mgAg-FANPs, 0.5mLCMCS solution and 0.5mLOKG solution were uniformly mixed at 25°C to obtain an outer layer Ag-FANPs-KGCM hydrogel solution.
[0079] (5) Preparation of C@Ag-KGCM bilayer hydrogel
[0080] The Ag-FANPs-KGCM hydrogel solution obtained in step (4) was quickly poured onto the gelled C-KGCM hydrogel obtained in step (3), and the solution was observed at 25°C and waited for gelation to obtain a C@Ag-KGCM double-layer hydrogel. The preparation process is shown in Figure 3, among which the gelation time is 4.5min.
[0081] Performance investigation of Ag-FANPs obtained in Example 1:
[0082] (1) Investigation of the photothermal properties of Ag-FANPs: 0.2, 0.4, 0.6, 0.8, and 1.0 mg / mL Ag-FANPs aqueous solutions were prepared, and a fiber-coupled diode laser system was used to induce the photothermal effect of Ag-FANPs. 2 ) irradiated Ag-FANPs aqueous solutions of different concentrations for 10 min, and an equal amount of pure water was used as a control. During the irradiation period, the temperature was recorded every 2 min using a Fotric 226S thermal imaging camera. The results are shown in Figure 4 and Figure 5 It can be seen that: as the concentration of Ag-FANPs increases, the temperature reached becomes higher. When the concentration of Ag-FANPs is 0.4 mg / mL, the temperature can reach about 55 °C, meeting the antibacterial requirements.
[0083] (2) In vitro antibacterial properties of Ag-FANPs: The antibacterial properties were evaluated by dilution coating plates. The concentrations of Ag-FA NPs were 0.2, 0.4, 0.6, 0.8, and 1.0 mg / mL, respectively. The photothermal group (+) NIR and the non-photothermal group (-) NIR were used. The photothermal group (+) NIR used 808 nm, 2.0 w / cm 2 The Ag-FANPs in each group were irradiated with near-infrared light for 10 min, and 1 mL of Staphylococcus aureus (S. aureus) or Escherichia coli (E.coil) suspension (10 6 CFU·mL -1 ) were mixed evenly, and the mixture was incubated in a shaker at 37°C and 100 rpm for 2 h. The control group was treated with sterile PBS buffer solution only. Non-photothermal group (-) NIR, the photothermal process was omitted, and the mixture was directly incubated in a shaker at 37°C and 100 rpm for 2 h. Then 100 μL of the bacterial suspension was spread on the MH broth solid culture medium. Finally, the plates obtained by the above two treatment methods were incubated at 37°C for 24 h, and photographed. The results are shown in Figure 6 and Figure 7 .
[0084] Performance investigation of Chlamydomonas reinhardtii in Example 1:
[0085] (1) Investigation of photosynthetic oxygen production performance of Chlamydomonas reinhardtii: 10 mL of algae cells were prepared at a concentration of 5×10 7 , 1×10 8 , 5×10 8 , 1×109 The algae solution was placed under 4000lx white light irradiation at an ambient temperature of 25°C, and the dissolved oxygen content in the algae solution was measured using a high-precision oxygen detector; 1×10 8 The Chlamydomonas reinhardtii solution was placed under 4000lx white light and in the dark, with the ambient temperature at 25°C, and the dissolved oxygen content was measured. The above measurement results are shown in Figure 8 , it can be seen that the algae cell concentration is 1×10 8 When the concentration of algal cells increases, the dissolved oxygen content reaches a maximum of 14.7 mg / L. As the concentration of algal cells increases, the dissolved oxygen content gradually decreases. Moreover, Chlamydomonas reinhardtii only produces oxygen under light conditions, and the dissolved oxygen content of the algal liquid will drop rapidly in a dark environment.
[0086] (2) Antioxidant capacity test of Chlamydomonas reinhardtii:
[0087] Determination of DPPH free radical scavenging ability: Algae cells were prepared at a concentration of 5×10 7 , 1×10 8 , 5×10 8 , 1×10 9 / mL of Chlamydomonas reinhardtii solution, prepare 0.4mol / L DPPH. Determination group: add 0.5mL DPPH to 1.0mL of different concentrations of algae solution, mix well and react at room temperature in the dark for 30 minutes, measure the absorbance at a wavelength of 517nm, and record it as Ai; similarly, control group: replace the algae solution with anhydrous ethanol, and record the absorbance as Ac; blank group: replace DPPH with 0.5mL anhydrous ethanol, and record the absorbance as Aj. The DPPH removal rate of Chlamydomonas reinhardtii at different concentrations was calculated according to the following formula, and the results are shown in the figure. Fig. 9 .
[0088]
[0089] Determination of ABTS free radical scavenging ability: Algae cells were prepared at a concentration of 5×10 7 , 1×10 8 , 5×10 8 , 1×10 9 Prepare 7.4 mol / L ABTS solution and 2.6 mol / L potassium persulfate solution from Chlamydomonas reinhardtii solution. Take 0.6 mL of each of the two solutions, mix them, keep them away from light, and place them at 4 °C for 12 h. Dilute the solution to OD 734=1.5. Test group: 1.0mL ABTS solution and 1.0mL algae solution were added in sequence, and the reaction was protected from light for 10 minutes. The absorbance at 734nm was measured and recorded using an ELISA instrument, which was recorded as A1. Similarly, the control group: 1.0mL algae solution was replaced with pure water, and the absorbance was recorded as A0. The blank group: 1.0mL ABTS was replaced with 1.0mL water, and the absorbance was recorded as A2. The ABTS clearance rate of Chlamydomonas reinhardtii at different concentrations was calculated according to the following formula. Fig. 9 .
[0090]
[0091] Determination of OH scavenging capacity: This experiment is based on Fe 2+ The ability of Chlamydomonas reinhardtii to remove superoxide anion ·OH was determined by the principle that it can react with H2O2 to produce hydroxyl radicals (·OH) by Fenton reaction. ·OH reacts with 3,3',5,5'-tetramethylbenzidine (TMB) to produce blue substances. The specific experimental process is as follows: First, the algae solution was centrifuged and the concentration of the algae solution was diluted to 5×10 7 , 1×10 8 , 5×10 8 and 1×10 9 / mL. Determination group: 0.01% H2O2 500μL, 0.75mmol / L FeCl2 500μL, 1mL algae solution and 50μL 12mmol / L TMB solution were added in sequence, reacted for 30min, and the absorbance at 652nm was measured and recorded using an enzyme reader, recorded as A2; similarly, control group: 1mL algae solution was replaced with 1mL HAc-NaAc buffer solution, the absorbance was measured and recorded as A0, blank group: 1mL HAc-NaAc buffer solution and 1mL algae solution were added in sequence, the absorbance was measured and recorded as A3. The OH removal rate of Chlamydomonas reinhardtii at different concentrations was calculated according to the following formula. The results are shown in Fig. 9 .
[0092]
[0093] O2 - Determination of scavenging ability: This experiment was based on the inhibition of superoxide dismutase by nitroblue tetrazolium (NBT) under light to determine the ability of Chlamydomonas reinhardtii to scavenge superoxide anions (·O2 - ) ability. In the presence of oxidizing substances, riboflavin can be reduced by light, and the reduced riboflavin can be easily reoxidized under aerobic conditions to produce O2 - , which can reduce NBT to blue methylhydrazone, which has a maximum absorption at 560nm, and SOD can remove O2 -, thus inhibiting the formation of methylhydrazone. Therefore, after the photoreduction reaction, the deeper the blue of the reaction solution, the more sensitive Chlamydomonas reinhardtii is to O2 - The lower the clearance rate, the higher the clearance rate. The specific experimental process is as follows: the concentration of Chlamydomonas reinhardtii was diluted or concentrated to 5×10 7 , 1×10 8 , 5×10 8 and 1×10 9 Prepare 5 reagents: reagent 1 is 0.05 mol / L phosphate buffer (PB), reagent 2 is 130 mmol / L methionine (Met), reagent 3 is 750 μmol / L nitroblue tetrazolium solution (NBT) (protect from light), reagent 4 is 100 μmol / L EDTA-Na2 solution, and reagent 5 is 20 μmol / L riboflavin solution (protect from light). Determination group: 100 μL of reagent 2, reagent 3, reagent 4 and reagent 5 were added to 1 mL of Chlamydomonas reinhardtii solution, and the absorbance at 560 nm was measured and recorded using an ELISA instrument after 20 minutes of 4000 lx illumination, which was recorded as A2; similarly, control group: 1 mL of PB solution was used to replace the Chlamydomonas reinhardtii solution, and the absorbance was recorded as A0; blank group 1: 1 mL of PB solution was used to replace the Chlamydomonas reinhardtii solution, and the reaction was carried out in the dark for 20 minutes, and the absorbance was recorded as A1; blank group 2: 400 μL of PB solution was added to 1 mL of Chlamydomonas reinhardtii solution, and the absorbance was recorded as A3. ·O2 of Chlamydomonas reinhardtii at different concentrations was calculated according to the following formula - Clearance rate, see Fig. 9 .
[0094]
[0095] Determination of H2O2 scavenging ability: This experiment is based on the principle that titanium sulfate will react with H2O2 to form a yellow precipitate, and the added sulfuric acid will dissolve the yellow precipitate, with maximum absorption at around 410nm to determine the ability of Chlamydomonas reinhardtii to scavenge hydrogen peroxide (H2O2). The specific experimental process is as follows: First, prepare a 0.5% titanium sulfate dilute sulfuric acid solution, and then prepare 0, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10mmol / L H2O2 standard solutions, take 1mL of H2O2 standard solution, add 400μL of titanium sulfate solution, use an enzyme reader to measure and record the absorbance at 410nm, and draw a standard curve of H2O2 concentration and absorbance at 410nm. Determination group: 500μL of 5×10 7 , 1×10 8 , 5×10 8 , 1×10 9Reinhardtia solution with 100 μL / mL was reacted with 2 mL 10 mmol / L H2O2 for 2 h, centrifuged to ensure that the algal cells were completely precipitated, and 1 mL of the supernatant was incubated with 400 μL titanium sulfate solution at 37 °C for 30 min, which was recorded as A. 测定 Similarly, for the control group, 500 μL of Chlamydomonas reinhardtii solution was replaced with aqueous solution and recorded as A 对照 . 对照 and A 测定 Substitute them into the standard curve to get the concentration value C of H2O2 对照 and C 测定 The H2O2 removal rate of Chlamydomonas reinhardtii at different concentrations was calculated according to the following formula. The results are shown in Fig. 9 .
[0096]
[0097] The mechanical properties of the double-layer hydrogel obtained in Example 1 were characterized by using a rotational rheometer with a fixture plate diameter of 20 mmol / L, a temperature setting of 32° C., and colloid loading.
[0098] (1) Frequency scanning test: The scanning angle frequency range is set to 0.1-100 rad / s, the tension is 6%, and the relationship between the mechanical properties of the colloid and the scanning angle frequency is tested. The results are shown in Fig.10 It can be seen that within the frequency range of 0.1-100 Hz, the storage modulus G' of the hydrogel is always greater than the loss modulus G", proving that it is always in a stable solid state.
[0099] (2) Step strain test: First, the hydrogel matrix was destroyed at a low constant strain of 50% for the first 60 seconds, and then at a higher strain of 500%. After that, the strain was readjusted to a constant low level of 50%, and repeated for four cycles. The results are shown in Fig.11 It can be seen that: in the process of hydrogel changing from low strain to high strain, both moduli decrease, proving that it has significant shear thinning ability, and after four cycles, the high strain hydrogel can recover to its original strength when the high strain is removed, indicating that it has good self-healing ability.
[0100] Other properties of the double-layer hydrogel obtained in Example 1 were investigated:
[0101] (1) Photothermal properties of double-layer hydrogels: KGCM blank hydrogel, C-KGCM inner layer hydrogel, Ag-FANPs-KGCM outer layer hydrogel, and C@Ag-KGCM double-layer hydrogel were prepared and photothermal performance was investigated using an 808 nm laser (2.0 W cm -2 ) was used to irradiate the hydrogel for 10 min. During the irradiation period, the temperature was recorded every 2 min using a Fotric 226S thermal imaging camera. Fig.12 and Fig.13, it can be seen that: the temperature of KGCM blank hydrogel and C-KGCM inner hydrogel hardly rises, while the temperature of Ag-FANPs-KGCM outer hydrogel can reach about 55 °C, and the temperature of C@Ag-KGCM double-layer hydrogel is slightly lower than that of Ag-FANPs-KGCM hydrogel alone, which can reach about 50 °C, and can still meet the antibacterial requirements.
[0102] (2) Investigation of the in vitro antibacterial properties of the double-layer hydrogel: The dilution plate method was used to investigate the in vitro antibacterial properties of the hydrogel. A PBS control group, a KGCM blank hydrogel group, a C-KGCM inner layer hydrogel group, an Ag-FA NPs-KGCM outer layer hydrogel group, and a C@Ag-KGCM double-layer hydrogel group were set up, which were further divided into a photothermal group (+) NIR and a non-photothermal group (-) NIR. The hydrogels in the above groups were immersed in 1 mL of a bacterial suspension of Staphylococcus aureus or Escherichia coli (10 6 CFU·mL -1 ). Photothermal group (+) NIR uses 808nm, 2.0w / cm 2 The hydrogels in each group were irradiated with near-infrared light for 10 minutes, and the mixture of the hydrogel and the bacterial suspension was incubated in a shaker at 37°C and 100 rpm for 2 hours; the non-photothermal group (-)NIR omitted the photothermal process, and the mixture of the hydrogels in each group and the bacterial suspension was directly incubated in a shaker at 37°C and 100 rpm for 2 hours, and then 100 μL of the bacterial suspension was taken and spread on the MH broth solid culture medium. The plates obtained by the above two treatment methods were incubated at 37°C for 24 hours, and photographed. The results are shown in Fig.14 and Fig.15 .
[0103] (3) Investigation of oxygen production performance of double-layer hydrogels: C. reinhardtii group, C-KGCM inner layer hydrogel group, (-)NIR C@Ag-KGCM non-photothermal double-layer hydrogel group, (+)NIR C@Ag-KGCM photothermal double-layer hydrogel group were set, and the algae cell concentration of each group was 1×10 8 / mL, the C. reinhardtii group diluted the algae solution 2 times, and the other three groups placed the hydrogel in the same volume of PBS solution, under 4000lx white light irradiation, the ambient temperature was 25℃, and the content of dissolved oxygen released into the PBS solution was measured using a high-precision active oxygen detector. The results are shown in Fig.16It can be seen that: compared with other groups, the dissolved oxygen content in the C. reinhardtii group increased faster. The reason for this was that the oxygen in the hydrogel consumed some time to be released into the PBS solution. The dissolved oxygen content in the C-KGCM inner layer hydrogel group did not decrease significantly compared with the C. reinhardtii group, and could still reach 14 mg / L. The C-KGCM inner layer hydrogel group > (-) NIR C@Ag-KGCM group > (+) NIR C@Ag-KGCM group. The dissolved oxygen in the (+) NIR C@Ag-KGCM group still showed an upward trend after photothermal treatment, indicating that some Chlamydomonas reinhardtii still survived and could continue to produce oxygen.
[0104] (4) Blood compatibility study of double-layer hydrogel: The following 6 groups were set up: negative control; KGCM; C-KGCM; Ag-FANPs-KGCM; C@Ag-KGCM; positive control. The positive control was treated with TritonX-100 solution only in the same way, and the negative control was treated with sterile saline only in the same way. Fresh blood was collected from the orbits of healthy SD rats, centrifuged, and washed with sterile PBS until the supernatant was clear, and then the red blood cell dispersion was diluted to 2%. The lyophilized products of each group of hydrogels were weighed and soaked in saline at 37°C for 24 hours to obtain hydrogel extracts (extraction concentration: 10 mg / mL). 500 μL of the extract, saline (negative control) and TritonX-100 solution (positive control) were taken respectively, and 500 μL of 2% red blood cell dispersion was added, mixed evenly, and incubated in a shaker at 37°C and 100 rpm for 1 hour. After the incubation, centrifuge and collect the supernatant. Use a microplate reader to measure and record the absorbance at 540nm. The absorbance of the negative control is AN; the absorbance of the positive control is AP; and the absorbance of the remaining groups of samples is AS. The hemolysis rate of different groups is calculated according to the following formula. The results are shown in Fig.17 .
[0105]
[0106] A hemolysis rate of less than 5% is considered to be good blood compatibility. Fig.17 It can be seen that only the positive control group induced by TritonX-100 solution showed hemolysis, and no hemolysis was observed in other groups, which proved that the prepared C@Ag-KGCM double-layer hydrogel had good blood compatibility.
[0107] The therapeutic effect of the double-layer hydrogel obtained in Example 1 on bacterial infection-type diabetic wounds in rats was investigated:
[0108] (1) Establishment of bacterial infection diabetic wound model
[0109] Before modeling, SD rats were fasted for at least 12 hours and weighed. Streptozotocin (STZ) was used and its instructions were modified to establish the type 1 diabetes model in SD rats. The STZ solution preparation process was to use pre-cooled citric acid buffer (pH = 4.2-4.5) to prepare a 1% (w / v) STZ solution, and filter and sterilize it with a 0.22μm microporous filter membrane. Pay attention to drying, avoiding light, and preparing it before use. Within 30 minutes, according to the body weight of fasting SD rats, 55mg·kg -1 The STZ solution was rapidly injected intraperitoneally at the given dose, and sufficient drinking water was ensured, normal feeding was performed, and bedding was changed frequently. After 3 days, blood was collected from the eye sockets, and the fasting blood glucose of SD rats was measured using a blood glucose meter. The fasting blood glucose of SD rats greater than 16.7 mmol / L was considered to be a successful establishment of the type 1 diabetes model. After the type 1 diabetes model was established, the bacterial infection wound model of diabetic rats was established. The back skin of SD rats was depilated and cleaned, and a full-thickness circular wound with a diameter of approximately 1.2 cm was created using sterilized surgical scissors. 10 7 CFU·mL -1 The wounds of diabetic rats were infected with a mixed bacterial suspension of Staphylococcus aureus and Escherichia coli (1 / 1, v / v).
[0110] (2) Treatment of bacterially infected wounds in diabetic rats by C@Ag-KGCM bilayer hydrogel
[0111] After establishing the bacterial infection diabetic wound model, C@Ag-KGCM double-layer hydrogel was used to treat the bacterial infection wounds of diabetic rats. Five groups were set up, namely the control group (PBS treatment), KGCM blank hydrogel group, Ag-FANPs-KGCM group (photothermal treatment on the first day, photothermal conditions 808nm near-infrared light 2w / cm 2 Light irradiation for 10 min), C-KGCM group (continuous irradiation of 4000 lx white light) and C@Ag-KGCM group (photothermal treatment + white light irradiation). The treatment process is shown in Fig.18 The wounds of SD rats with bacterial infection and diabetes were photographed on day 0, day 1, day 4, day 7, day 10, and day 13 to observe their healing status. The results are shown in Fig.19 and Fig. 20 .from Fig.19 and Fig. 20It can be seen that bacterial infection diabetic wounds are always difficult to heal without treatment. The wounds of the PBS-treated control group and the KGCM blank hydrogel group healed slowly from the 1st day to the 13th day, and the wounds had not healed on the last day; but under the treatment of the Ag-FANPs-KGCM group, the C-KGCM group and the C@Ag-KGCM group, the area of the bacterial infection diabetic wounds of diabetic rats was visually significantly reduced on the 4th day, the 7th day, the 10th day, and the 13th day. Compared with the control group, the wounds healed faster, and the wounds were basically completely healed on the last day, with the best healing condition. The above results show that the C@Ag-KGCM double-layer hydrogel has excellent ability to promote the healing of bacterial infection wounds in diabetic rats.
Claims
1. A self-healing double-layer hydrogel for promoting diabetic wound healing, characterized in that: The hydrogel comprises an inner and outer layer, wherein the inner layer is a self-healing hydrogel in which microalgae cells are evenly distributed, and the outer layer is a self-healing hydrogel in which metal ion-humic acid coordinated nanoparticle complexes are evenly distributed. The self-healing hydrogel is formed by self-crosslinking of a macromolecular polymer containing an aldehyde group and a macromolecular polymer containing an amino group.
2. The double-layer hydrogel according to claim 1, characterized in that: The preparation method of the metal ion-humic acid coordinated nanoparticle complex is: adding humic acid aqueous solution dropwise into metal ion compound aqueous solution, stirring at 500-1000 rpm for 3-4 hours, centrifuging, washing the precipitate with water twice or more, and freeze-drying to obtain the metal ion-humic acid coordinated nanoparticle complex.
3. The double-layer hydrogel according to claim 1, characterized in that: The microalgae cells are one or more of Cyanobacteria, Chlorophyta, Rhodophyta, Phaeophyta, Cryptophyta, Dinophyta, Chrysophyta, Xanthophyta, Bacillariophyta, Euglenophyta and Charophyta; the macromolecular polymer containing aldehyde groups is one or more of oxidized hyaluronic acid, oxidized sodium alginate, oxidized konjac glucan and oxidized dextran; the macromolecular polymer containing amino groups is one or more of carboxymethyl chitosan, chitosan and polylysine.
4. The method for preparing the metal ion-humic acid coordinated nanoparticle complex according to claim 2, characterized in that: The mass volume ratio of the metal ion compound to the aqueous solution is 0.5 g:10-40 mL, and the mass volume ratio of the humic acid to the aqueous solution is 0.5 g:10-40 mL.
5. The method for preparing the metal ion-humic acid coordinated nanoparticle complex according to claim 2, characterized in that: The metal ions are one or more of gold, platinum, ruthenium, rhodium, iridium, silver, copper and iron ions; the humic acid is one or more of humic acid, fulvic acid and humin.
6. The double-layer hydrogel according to claim 1, characterized in that: The condition for the inner layer hydrogel to exert photosynthetic oxygen production is a light intensity of 2000-5000 lx; the condition for the outer layer hydrogel to exert photothermal antibacterial effect is irradiation with near-infrared light with a wavelength of 808 nm.
7. The method for preparing the double-layer hydrogel according to claims 1 to 6, characterized in that: The following steps are involved: Step 1: adding a certain amount of live microalgae cells to a polymer macromolecular solution containing an aldehyde group to obtain a mixed solution A, and then adding a polymer macromolecular solution containing an amino group to the mixed solution A, cross-linking at room temperature, to obtain an inner layer hydrogel with antioxidant and photosynthetic oxygen production effects; Step 2: Add a certain amount of metal ion-humic acid coordinated nanoparticle complex to the polymer macromolecular solution containing aldehyde groups to obtain a mixed solution B, and then add the polymer macromolecular solution containing amino groups to the mixed solution B to obtain an outer layer hydrogel solution with photothermal antibacterial effect, which is then quickly poured onto the gelled inner layer hydrogel obtained in step 1, and continue to cross-link at room temperature to obtain a self-healing double-layer hydrogel that promotes diabetic wound healing.
8. The method for preparing the double-layer hydrogel according to claim 7, characterized in that: In step 1, the concentration of live microalgae cells is 5×10 7 ~5×10 8 / mL, the concentration of the polymer macromolecule solution containing aldehyde groups is 0.5-3wt%, and the concentration of the polymer macromolecule solution containing amino groups is 3-6wt%; in the step 2, the concentration of the metal ion-humic acid coordinated nanoparticle complex is 0.4-2mg / mL, the concentration of the polymer macromolecule solution containing aldehyde groups is 0.5-3wt%, and the concentration of the polymer macromolecule solution containing amino groups is 3-6wt%.
9. The method for preparing the double-layer hydrogel according to claim 7, characterized in that: The solution systems are all phosphate buffer solution systems with a pH of 7-8.
10. Use of the self-healing double-layer hydrogel for promoting diabetic wound healing according to claim 1 in preparing chronic diabetic wound dressings.
Citation Information
Cited By
Gel dressing based on algae particles and capable of promoting wound healing as well as preparation method and application of gel dressing
CN119971131A
An algal particle-based gel dressing that can promote wound healing and its preparation method and application
CN119971131B
Spatial separation double-layer hydrogel as well as preparation method and application thereof
CN120227462A
A spatially separated double-layer hydrogel and its preparation method and application
CN120227462B
Multifunctional microalgae-based hydrogel wound dressing as well as preparation method and application thereof
CN122440885A